Six Sigma logistics: application in the warehouse of a miningunit - Tinoco Ángeles, Felix Enrique (2013)
This article deals with the application of a modern tool total quality management: Six Sigma, logistics of a mining company located in the central highlands of Peru. The implementation of the first four phases of the DMAIC cycle is detailed, variables in which the organization should focus its efforts to reduce the defect been identified initially defined.